Constitutional Complaint Sebagai Mekanisme Pengawasan Terhadap Penyalahgunaan Diskresi Oleh Aparat Pemerintahan Melalui Mahkamah Konstitusi - Christabel Pratama; Firly Tabita Nasuha; Orlyn Permata Dinova; Andhika Tedja; Aliya Salsabila Bisri (Fakultas Hukum, UPN Veteran Jawa Timur, 2025)
The 1945 Constitution of the Republic of Indonesia (UUD 1945) establishes the constitutional legitimacy of the Constitutional Court (MK) in exercising its authority to review laws against constitutional principles. The widespread misuse of administrative discretion by government officials has become a deeply rooted issue in Indonesia. A constitutional complaint serves as a remedy implemented in several developed countries, such as Germany, to address situations in which individuals feel harmed by government actions or policies. Unfortunately, there is no implementation of constitutional complaint in Indonesia. This mechanism is also consistent with the values contained in the 1945 Constitution and remains within the scope of the Constitutional Court’s functions. Introducing a constitutional complaint mechanism in Indonesia through the Constitutional Court is essential to ensure stronger protection of citizens’ constitutional rights. This study employs a normative juridical method, relying on statutory regulations supported by previous scholarly works. Keywords: Constitutional Complaint; Constitutional Court; Discretion